2015
DOI: 10.1614/ipsm-d-14-00046.1
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Timeframe for Rapid Response and Best Management Practices of Flood-Dispersed Japanese Knotweed (Fallopia japonica)

Abstract: The objective of this article is to extend the reported period in which flood-distributed knotweed propagules may be successfully managed using only manual labor. During a second round of early detection and rapid response (EDRR) management along the Green River in Guilford, VT, we collected and measured all Japanese knotweed propagules that had been distributed by flooding approximately 21 mo earlier, in August 2011, at a single site. Our data suggest that knotweed s.l. prioritizes the growth of new stems ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…There is a broad consensus that plant invasion will increase, and is already increasing due to climate change (Clements and DiTommaso, 2011;DiTommaso et al, 2014;Varanasi and Jugulam, 2016;Ramesh et al, 2017;Waryszak et al, 2018;Ziska et al, 2019). Three prominent predictions are: (1) poleward spread due to climate warming (Clements and DiTommaso, 2011), (2) range expansion due to changing precipitation regimes (Young et al, 2017), and (3) increased dispersal and establishment due to extreme climate events (Colleran and Goodall, 2015). Below we provide examples of these three predicted consequences of climate change, as well as the potential influence of rapid weed evolution as part of the response.…”
Section: Recent Examples Of Increased Invasion Under Climate Changementioning
confidence: 99%
“…There is a broad consensus that plant invasion will increase, and is already increasing due to climate change (Clements and DiTommaso, 2011;DiTommaso et al, 2014;Varanasi and Jugulam, 2016;Ramesh et al, 2017;Waryszak et al, 2018;Ziska et al, 2019). Three prominent predictions are: (1) poleward spread due to climate warming (Clements and DiTommaso, 2011), (2) range expansion due to changing precipitation regimes (Young et al, 2017), and (3) increased dispersal and establishment due to extreme climate events (Colleran and Goodall, 2015). Below we provide examples of these three predicted consequences of climate change, as well as the potential influence of rapid weed evolution as part of the response.…”
Section: Recent Examples Of Increased Invasion Under Climate Changementioning
confidence: 99%
“…During removal of flood‐distributed knotweed s.l . propagules (Colleran & Goodall, 2014, 2015), we found that removing newly established plants by hand was fastest; the lack of root hairs aided in sifting plants directly from the ground. From results showing (a) underground rhizomes as the predominant source of new knotweed s.l .…”
Section: Introductionmentioning
confidence: 76%
“…Likewise, invasions of SMFFs that are not already dominated by F. japonica should be prevented by early detection and rapid removal of new propagules/colonists (e.g. Colleran and Goodall 2014 , Colleran and Goodall 2015 ). In addition to F. japonica , our results suggest these efforts should account for other invasive species that have become prominent in the region, particularly Alliaria petiolata (M.…”
Section: Discussionmentioning
confidence: 99%